Bold Responses to Inhibition in Cannabis Using Adolescents and Emerging Adults - (:unkn) unknown (My University, 2019)
Cannabis use has been associated with increased blood oxygen level dependent (BOLD) responses absent of behavioral deficits during a response inhibition task compared to controls. We investigated whether gender and cannabis use result in differences in BOLD responses and behavioral performance during a Go-NoGo task. Participants included eighty-three 16-26 year olds (MJ=36, Controls=46). An emotion based Go-NoGo task required participants to inhibit their response during a “neutral” face. A whole-brain analysis looked at differences between cannabis group, gender, and their interaction. Significant increased BOLD responses were observed in cannabis users compared to controls in the left frontal cortex, left cingulate cortex, and the left thalamus during correct response inhibitions. There were no significant differences on task performance or group by gender interactions. Supporting previous research, cannabis users showed increased BOLD responses in core areas associated with response inhibition during a Go-NoGo task further elucidating the relationships between cannabis and brain-behavior.
Keywords: Adolescents; BOLD Responses; Cannabis Use; Response Inhibition